A seed motif for target RNA capture enables efficient immune defence by a type III-B CRISPR-Cas system. Issue 9 (2nd September 2019) - Pan, Saifu; Li, Qi; Deng, Ling; Jiang, Suping; Jin, Xuexia; Peng, Nan; Liang, Yunxiang; She, Qunxin; Li, Yingjun
ABSTRACT: CRISPR-Cas systems provide an adaptive defence against foreign nucleic acids guided by small RNAs (crRNAs) in archaea and bacteria. The Type III CRISPR systems are reported to carry RNase, RNA-activated DNase and cyclic oligoadenylate (cOA) synthetase activity, and are significantly different from other CRISPR systems. However, detailed features of target recognition, which are essential for enhancing target specificity remain unknown in Type III CRISPR systems. Here, we show that the Type III-B Cmr-α system in S. islandicus generates two constant lengths of crRNA independent of the length of the spacer. Either mutation at the 3ʹ-end of crRNA or target truncation greatly influences the target capture and cleavage by the Cmr-α effector complex. Furthermore, we found that cleavage at the tag-proximal site on the target RNA by the Cmr-α RNP complex is delayed relative to the other sites, which probably provides Cas10 more time to function as a guard against invaders. Using a mutagenesis assay in vivo, we discovered that a seed motif located at the tag-distal region of the crRNA is required by Cmr1α for target RNA capture by the Cmr-α system thereby enhancing target specificity and efficiency. These findings further refine the model for immune defence of Type III-B CRISPR-Cas system, commencing on capture, cleavage and regulation.